POLA KONSUMSI JAJAN, STATUS GIZI DAN PRESTASI BELAJAR SISWA SD NEGERI 064027 KECAMATAN MEDAN POLONIA - Imaniar Hasibuan; Mhd.Arifin Siregar; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT Nutritional needs of primary school children was obtained from the main meal and snack food. Good food intake will affect the nutritional status of children, related to the immune system, the level of attendance, concentration and the ability to follow the lessons in the school so that the impact on learning achievement. This study aims to determine the pattern of snack consumption, nutritional status and student achievement in SDN 064 027 District of Medan Polonia. This study used a cross sectional design. The population is all fifth grade students aged 10-12 years SDN 064 027 District of Medan Polonia. Samples were taken as many as 103 students of class V aged 10-12 years with a total sampling technique. Primary data was collected by interviews using questionnaires, 24-hour food recall forms, food frequency form, measurement of weight and height. Secondary data were collected from the description of the school, attendance, report grades students. The results showed that the types of snacks consumed in a week with a daily frequency is soft drinks/bottled, frequency is often soft drinks/bottled and fried, frequency is a rare savory rice and fried rice, frequency is never guava. Energy consumption in the snack food category is not enough as big as 59.2%, protein snack food consumption in enough categories at 63.1%. Snack food in male respondents accounted for 19.0% energy and 13.5% protein from total consumption a day, the female respondents accounted for 17.9% of energy and 14.1% protein from the total consumption a day. Nutritional status by indicator IMT/U and TB/U is in normal category respectively 75.5% and 71.8%. Learning achievement in enough categories was 42.7%. It is recommended to the school in order to convey to the parents to pay attention to major food consumption in terms of quantity and diversity as well as choosing calorie-dense snack foods. The school is also expected to pay attention and control the types of snacks sold in the school in order to ensure safety, cleanliness, diversity. Keywords: Snack Consumption, Nutritional Status, Learning Achievement